Optimization of Sinom and Lime Tea Bag Formulation Using D-Optimal Mixture Design: Physicochemical and Sensory Evaluation - Ni Ketut Wiradnyani; I Made Yoga Parwata (Journal of Health and Nutrition Research, 2026)
Sinom is a traditional beverage composed of turmeric (Curcuma longa) and young tamarind leaves (Tamarindus indica L.), recognized for its phenolic compounds. To address the limited shelf-life of liquid, ready-to-drink Sinom mixed with lime, this study aimed to develop a more practical, dip-type (tea-bag) formulation. A D-Optimal Mixture Design was applied to optimize the ratio of three dry ingredients: young tamarind leaf powder, lime powder, and turmeric powder. The optimization determined an ideal mixture ratio of 48.393 : 18.607 : 33.000 (% w/w), respectively, achieving a desirability value of 0.772. Physicochemical evaluation of the optimized prototype demonstrated a relatively low moisture content (9.572 ± 0.33%), which theoretically supports storability, and an acidic profile (pH 3.33 ± 0.0186). Colorimetry yielded L*, a*, and b* values of 31.9 ± 0.20, 0.9 ± 0.14, and 15.3 ± 0.13. The antioxidant capacity was moderate, indicated by a DPPH IC₅₀ value of 238.067 ppm and a total polyphenol content of 14.392 ± 1.12 mg GAE/g. Furthermore, hedonic sensory evaluation revealed a moderate overall consumer acceptance (scored 3.292), with the beverage's color receiving the highest preference rating. In conclusion, the D-Optimal Mixture Design successfully produced a ready-to-brew herbal tea candidate with acceptable physicochemical parameters and moderate functional properties. While this dry formulation presents a practical alternative to liquid preparations, further comprehensive investigations—specifically regarding shelf-life profiling, microbiological safety, and cost evaluations—are essential before establishing definitive claims about its long-term stability or market readiness.